The application of artificial intelligence in constitutional processes for the protection of fundamental rights - Tupayachi Sotomayor, Jhonny (2024)
This article aims to reflect on the implementation of artificial intelligence in constitutional processes, specifically in amparo and habeas corpus proceedings against judicial rulings, and the aporia that such an approach would entail, given that it is currently a complex task for claimants to determine the violation of constitutionally protected fundamental rights within ordinary judicial processes. This implies that when such processes are constitutionalized, they may fail to merit a substantiated judgment, as inadmissibility often becomes a decisive factor. From this perspective, an intriguing question arises: Would the implementation of artificial intelligence be effective in resolving constitutional processes that challenge judicial decisions, particularly from the standpoint of protecting fundamental rights and ensuring effective procedural safeguards? Answering this question requires examining the relationship between law and artificial intelligence (AI) and identifying the issues within the mentioned constitutional processes to assess whether AI could provide a solution to the existing problem.